2017
DOI: 10.1016/j.theriogenology.2016.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The use of semi-quantitative tests at Cesarean section delivery for the differentiation of canine fetal fluids from maternal urine on the basis of biochemical characteristics

Abstract: In dogs, there is no diagnostic test to identify and differentiate fetal fluids from maternal urine in the event that a clear-yellowish vulvar discharge is observed pre-whelping. The objective of this study was to find a test that could easily and accurately identify rupture of the fetal membranes preceding parturition. Maternal urine, and amniotic fluid (AMF) and allantoic fluid (ALF) from only one fetus per bitch, were collected intraoperatively during Cesarean section. Specific gravity (SG) was analyzed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
8
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 35 publications
9
8
2
Order By: Relevance
“…In 2021, Tal et al [ 5 ] demonstrated the possibility to easily and safely perform amniocentesis in anesthetized bitches at around 35–62 days of pregnancy. Moreover, at the time of parturition, when caesarean section is performed, fetal fluids (amniotic and allantoic) can be easily and securely sampled, as demonstrated by many studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Other than that, the canine fetal fluids were also useful for mesenchymal stem cells isolation and growth as a model of these cell’s biology study and for possible therapeutic application [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Tal et al [ 5 ] demonstrated the possibility to easily and safely perform amniocentesis in anesthetized bitches at around 35–62 days of pregnancy. Moreover, at the time of parturition, when caesarean section is performed, fetal fluids (amniotic and allantoic) can be easily and securely sampled, as demonstrated by many studies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Other than that, the canine fetal fluids were also useful for mesenchymal stem cells isolation and growth as a model of these cell’s biology study and for possible therapeutic application [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…They were immediately evaluated by commercial dipsticks (Combur-Test ® , Roche Diagnostic Limited, Mannheim, Germany) for SG, pH, leukocytes, nitrites, glucose, proteins, ketones, urobilinogen, bilirubin, and blood. Following the technique reported by Balogh et al [4], a drop of urine was put on each field of the strip and, after dripping, the results were read after 60 seconds for all the parameters, except for leukocytes that were read at 120 seconds. For each parameter, the results were recorded using the visual reference colorimetric scale reported by the company ( Table 1).…”
Section: Sample Collection and Urinalysismentioning
confidence: 99%
“…Few studies looked for markers of neonatal homeostasis, but they still cannot be widely applied in everyday veterinary clinical practice: lactate, glucose and beta-hydroxybutyrate levels were correlated to neonatal mortality [3]; the Combur test analysis on glucose and ketones in the fetal fluids collected at C-section was described [4]; the composition of the fetal fluids at C-section was linked to neonatal mortality and viability [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations